Al-Ghazali’s Theory of Resilience: A Tawakkul-Based Islamic Therapeutic Approach for Bullying Victims - Jumardi Hasan; Ahmad Farhan Nasution; Hirzan Humaidi (LaKaspia, 2025)
Bullying phenomena in Indonesia, particularly among students, demonstrate a high prevalence and generate serious psychological consequences for victims, including depression and suicidal tendencies. Objective: This study aims to explore the role of the concept of tawakkul in enhancing the resilience of bullying victims. Method: This research employs a qualitative approach with descriptive analysis through a literature review that includes indexed scientific articles, books, online media sources, and other reliable academic references. Results: The findings indicate that tawakkul, from the perspective of al-Ghazali, contributes to strengthening individual resilience through dimensions of spirituality, self-acceptance, and complete trust in divine decree. Conclusion: This study asserts that tawakkul may function as an Islamic-based psychotherapeutic approach to support psychological recovery among bullying victims. In conclusion, tawakkul has the potential to serve as a therapeutic foundation for improving resilience and preventing long-term psychological impacts.